Journal of technical education seience (Ho Chi Minh city University of Technology and Education, 2021)
Contents: Production of bacterial cellulose films by Gluconoacetobacter xylinus for lipase immobilzation; building climate change adaptation indicator set for Moc Hoa district, Long An province; research technology of cultivation of spirulina algae with the use of CO2 hidden from the smoke of rice husk boiler; effect of enthanol treatment on morphological and technical properties of corn starch;....